Polarized location of SLC and ABC drug transporters in monolayer-cultured human hepatocytes. Issue 5 (August 2015) - Le Vee, Marc; Jouan, Elodie; Noel, Gregory; Stieger, Bruno; Fardel, Olivier
Highlights Monolayer-cultured human hepatocytes retain notable drug transporter mRNA expression. OATPs, OCT1 and MRP3 are detected at the sinusoidal pole of cultured hepatocytes. P-glycoprotein and MRP2 are expressed at the canalicular pole of cultured hepatocytes. Uptake transport is maintained in long-term monolayer-cultured human hepatocytes. Canalicular secretion is maintained in 10 day monolayer-cultured human hepatocytes.